Analysis on the Effects of Housing Relevant Taxation as a Macroprudential Policy Tool - Jang, Hun (2021)
This study conducted a comprehensive analysis on the impact of housing relevant taxations on the target variables of financial stability such as house price and credit levels while considering its adverse impact on the output and welfare differences between households. Thereby, the study has analyzed its effectiveness as a macroprudential policy tool and checked financial stability. It has been shown that a tax rate increase, whether it is temporal or permanent, can effectively lower house prices and credit levels. Even if there was an early decline in output level after the changes in the tax rate, this adverse effect can be mitigated in the medium run due to capital accumulation. Also, setting a proper tax rule by considering the house price increase can stabilize the housing market when there is a positive housing preference shock or a productivity shock. However, welfare changes between households were not be fairly distributed after each tax policy implementation. Therefore, it is advisable for the policy authority to combine an appropriate redistribution scheme with taxation by paying attention to the potential welfare changes of the households when they choose to use housing taxation in pursuing of macro-financial stability.